Attention bias modification for depression: A systematic review and meta-analysis - Xia, Hai-sha; Li, Yu-xi; Zhang, Qing-yun; Zhong, Dong-ling; Liu, Xiao-bo; Gou, Xin-yun; Fan, Jin; Zhao, Jing; Zhang, Yue; Ai, Shuang-chun; Huang, Jia-xi; Li, Juan; et al. (Frontiers in Psychiatry, 2023)
Background: Depression is a mental health disorder characterized by affective, somatic, and cognitive symptoms. Attention bias modification (ABM) has been widely used to treat depression. However, the results seem inconsistent. We conducted a systematic review and meta-analysis to investigate the efficacy of ABM for depression and to explore the optimal protocol of ABM. Methods: Seven databases were systematically searched from their inceptions to October 5, 2022, to include randomized controlled trials (RCTs) of ABM for depression. Two independent reviewers selected the eligible articles, extracted data, and evaluated the risk of bias using version 2 of the Cochrane risk-of-bias tool (ROB 2.0) tool for randomized trials. The primary outcome was the evaluation of depressive symptoms using widely accepted and validated scales. The secondary outcomes included rumination, and attentional control. Results: Nineteen trials involving 20 datasets (1262 participants) were included. The overall risk of bias in 1 study were rated as low risk of bias, 3 were considered as high, and the remaining were some concerns. Compared with attention control training (ACT), ABM had greater effect in improvement of depression (SMD = −0.48, 95%CI −0.80 to −0.17, I2 = 82%) and rumination (MD = −3.46, 95%CI −6.06 to −0.87, I2 = 0%). No significant differences were observed in the attentional control outcome between ABM and ACT (MD = 3.07, 95%CI −0.52 to 6.65, I2 = 0%). Subgroup analysis demonstrated that adults exhibited a greater decrease of depression scores than adolescents. ABM using dot-probe task, training target stimulus presented by face and training directions by left-right were associated with better antidepressant effects. ABM training delivered in the laboratory tended to yield better effect than those conducted at home. Sensitivity analysis indicated the above results were robust. The certainty of evidence for all outcomes was low or very low, and publication bias may exist. Conclusion: Due to high heterogeneity and limited studies, no enough current evidence supported that ABM could be an effective intervention to relieve depressive symptoms. More rigorous RCTs are required to verify the benefits and to explore the optimal protocol of ABM training for depression.